Gastrointestinal symptoms from an epidemiological perspective. Issue 6 (24th May 2021) - Quadflieg, Norbert
Abstract: Four manuscripts on gastro‐intestinal problems or disorders of gut‐brain interaction are discussed from an epidemiological perspective. A literature review with strict inclusion criteria pointed out the dearth of evidence‐based knowledge on gastrointestinal symptoms following treatment for anorexia nervosa. An epidemiological follow‐up study showing the relevance of childhood abdominal pain for fasting to control weight in adolescence is used to emphasize the need to refine our approach to risk factor research in eating disorders. Two additional studies highlight the high prevalence of gastro‐intestinal problems in eating disorders underscoring a need for improved consideration of these symptoms in clinical practice and eating disorder research.